A Christmas carol - Kennedy, Pamela, 1946-; Heyer, Carol, 1950-; Dickens, Charles, 1812-1870. (Nashville, Tenn. : Ideals Children's Books, 1995)
A simplified retelling of how the miserly Scrooge learns the true meaning of Christmas when three ghostly visitors review his past and foretell his future.
Keywords: Christmas -- Fiction; Ghosts -- Fiction; England -- Fiction